ANALISIS LAPORAN KEUANGAN DALAM MENILAI KINERJA KEUANGAN PT MARK DYNAMICS INDONESIA TBK - Supia Lorensa Situmorang; Zulia Rifda Daulay (ADISAM PUBLISHER, 2023)
This research aims to find out how the company's financial performance at PT. Mark Dynamics Indonesia Tbk in terms of liquidity ratios, solvency ratios, profitability ratios and activity ratios. The type of research used in this research is quantitative research with a descriptive approach. The data processed is the financial report of the company PT. Mark Dynamics Indonesia Tbk for the period 2019 - 2022. The analysis technique used is quantitative analysis where this analysis uses data processing in the form of numbers as a tool for analyzing and conducting studies. Then a time series analysis is carried out, namely an analysis by comparing financial ratios from one period to another, where the ratio analysis used is financial ratio analysis consisting of liquidity ratios, solvency ratios, profitability ratios and activity ratios. With the research results from the liquidity ratio seen from the current ratio and fixed ratio, the company is in good condition, from the solvency ratio seen from the debt to assets ratio and debt to equity ratio, the company is in healthy condition, and from the profitability ratio seen from the gross profit margin ratio , net profit margin, operating profit margin, return on assets ratio, and return on equity ratio, the company is in good and healthy condition in making profits. And from the activity ratio seen from the asset turnover ratio, working capital turnover ratio, fixed asset turnover ratio, and inventory turnover ratio, the company is in poor condition because the percentage in this ratio decreases every year.